Photoinduced Core Skeletal Editing: Streamlined Strategies for the Synthesis of Diverse Cyclic Scaffolds - Singhal, Anukriti; Tiwari, Kajal; Choudhury, Swagata; Roy, Sudipta Raha (Synlett, 2025)
Skeletal editing is a novel approach for the synthesis of diverse molecular scaffolds that is currently under investigation in the field of drug discovery and modern synthetic chemistry. With the rise of photochemistry, recent years have witnessed significant progress in the development of new photochemical skeleton editing methods, encompassing the atom-swap, inclusion, or exclusion of single or multiple atoms, thereby facilitating the discovery and development of several complex bioactive molecules. Considering their importance, we have summarized a comprehensive overview of the various photochemical skeletal editing methodologies that have been developed by various research groups, including us. Through this account, we anticipate that it will emphasize not only the innovative nature of existing skeleton editing technologies but also the vast opportunities that lie ahead in this emerging field.
Keywords: Skeletal editing; Single-atom swap; Ring expansion; Ring contraction; Heterocycle synthesis